Correlation analysis of Safflower genotypes for yield and yield contributing traits over the locations: Correlation analysis of Safflower genotypes for yield and yield contributing traits over the locations - A H RATHOD; S B GHUGE; D K ZATE; A S MALVE; S L SHINDE (Journal of Oilseeds Research, 2023)
Twelve genotypes were used in the field experiments, which were carried out at the four different locations. Out of thirteen morphological characters there was positive correlation between yield and the test weight, the number of seeds/capitulum, the days to maturity, the number of seeds/capitulum and days to 50% flowering.